Biocontrol of soil diseases and soil profile associated with rhizosphere of rice (Oryza sativa Subsp. Japonica) growing paddy fields in Kansai region, Japan. (3rd July 2020) - Dilzahan, Hosne Ara; Yoshida, Masaaki; Umeda, Maya; Calubaquib, Michelle Ann; Organo, Nolissa Delmo; Cruz, Andre Freire
ABSTRACT: This research focused on in vitro and in vivo biocontrol of two major rice diseases, Bacterial Leaf Blight caused by Xanthomonus oryzae pv oryzae ( Xoo ) and Sheath Blight caused by Rhizoctonia solani . Furthermore, the soil of paddy fields in Kansai region, Japan was analysed for the presence of these pathogens, and their microbial communities were evaluated according to the location and management systems. For biocontrol, the rhizospheric bacteria were isolated and molecularly identified. The results indicated that DAR17225040 and DAR17225017 were 99% similar to Bacillus aryabhattai and Bacillus megaterium . The isolated bacteria were able to suppress Bacterial Leaf Blight and Sheath Blight disease 78% and 86% respectively, under greenhouse conditions. The 16S amplicon sequencing (Illumina MiSeq 250bp) was used to analyse the bacterial community in paddy fields of soil taken from five locations under conventional and organic systems. Xoo and R. solani were detected in sampled soil, however, no clear difference was noted, regarding systems. From amplicon sequencing data, Chloroflexi, Acidobacteria, Proteobacteria, Actinobacteria, Planctomycetes were the dominant phyla of rice soil in Kansai region. The phylum Kazan-3B-28 was found more in organic system than conventional. The bacterial community was more affected by location and soil type than by management systems.